A method for preparing heterojunction silver paste
By using organic solvents, methacrylic modified epoxy resins and oxide nanoadditives to prepare heterogeneous silver paste, the conductive properties and stability of silver paste in heterogeneous solar cells are solved, and high efficiency and low cost are achieved silver paste preparation, suitable for a variety of electronic devices.
Patent Information
- Application Number
- CN202410341461.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-03-25
AI Technical Summary
In the prior art, silver paste in heterojunction solar cells has poor conductivity, weak adhesion and poor stability, cumbersome preparation process and high cost, making it difficult to meet the needs of high-end applications.
Heterogenous silver paste is prepared by organic solvents, methacrylic modified epoxy resins, additives and oxide nanoadditives. The dispersion, conductivity and stability of the silver paste are improved through specific ratios and process flows to form a tight The silver paste/substrate interface improves conductivity and photoelectric conversion efficiency.
It has achieved the preparation of heterogeneous silver paste with good adhesion, high filling factor and good wetting properties, which has reduced production costs, improved photoelectric conversion efficiency and battery conductivity, and is suitable for a variety of electronic devices.
Smart Images

Figure BDA0004756956590000211 
Figure BDA0004756956590000221
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cells, and in particular to a method for preparing heterojunction silver paste. Background Art
[0002] With the continuous advancement of science and technology, silver paste, as an important conductive material, is increasingly used in the fields of electronics, photovoltaics, touch screens, printed circuit boards, etc. Especially in the field of heterojunction solar cells, silver paste, as an electrode material, plays a vital role in improving the photoelectric conversion efficiency and long-term stability of the battery. However, traditional silver paste preparation methods usually use physical mixing or simple chemical synthesis methods. The silver paste prepared by these methods often has problems such as poor conductivity, weak adhesion, and poor stability, which limits its wide application in heterojunction solar cells.
[0003] In order to solve these problems, researchers have conducted extensive research on the preparation technology of silver paste and proposed a variety of preparation methods and modification methods. For example, by adding different surfactants, dispersants or nanoparticles to improve the dispersibility and conductivity of silver paste. Although these methods have improved the performance of silver paste to a certain extent, there are still problems such as cumbersome preparation process, high cost and insufficient stability.
[0004] In recent years, with the rapid development of nanotechnology, using nanomaterials to improve the performance of silver paste has become a research hotspot. Nanomaterials have excellent physical and chemical properties, such as high specific surface area, good conductivity and stability, which provide new possibilities for improving the performance of silver paste. However, how to effectively introduce nanomaterials into silver paste and ensure their uniform distribution in the silver paste is still a major challenge facing current technology.
[0005] Therefore, developing a simple, efficient and low-cost method for preparing heterojunction silver paste has become an urgent problem to be solved. This method needs to be able to prepare silver paste with good dispersibility, high conductivity and long-term stability to meet the application requirements of high-end fields such as heterojunction solar cells.
[0006] Based on the above background, the present invention proposes a new method for preparing heterojunction silver paste, aiming to solve the problems existing in the prior art and provide more reliable technical support for the application of silver paste in the field of heterojunction solar cells. Summary of the invention
[0007] The object of the present invention is to provide a simple, efficient and low-cost method for preparing heterojunction silver paste.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] A method for preparing a heterojunction silver paste, comprising the steps of:
[0010] (1) mixing 8-14 parts of an organic solvent, 2-6 parts of a methacrylic acid-modified epoxy resin, and 2-10 parts of an auxiliary agent at 40-50° C. and stirring for 40-60 minutes, and then cooling to room temperature to obtain an organic carrier;
[0011] (2) mixing 20-95 parts of silver powder and 10-15 parts of oxide nano additives with the organic carrier prepared in step (1), and stirring and mixing them uniformly to prepare a silver paste;
[0012] The auxiliary agent includes a thickener, a toughening agent, a thixotropic agent, a surfactant and a wetting and dispersing agent in a weight ratio of (1-4): (2-4): (2-5): (1-5): (1-5).
[0013] Preferably, the organic solvent comprises terpineol, tributyl citrate and ethyl acetate in a mass ratio of (2-3):(1-3):(1-2).
[0014] Preferably, the preparation method of the methacrylic acid modified epoxy resin comprises: using 30-35 parts of methacrylic acid as a functional monomer, 0.7-1wt% of benzoyl peroxide as an initiator, 25-28 parts of butyl acrylate, 5-8 parts of styrene as raw materials and 10-14 parts of epoxy resin, carrying out graft polymerization in the presence of 35-42 parts of a solvent, the reaction temperature is 110-120° C., the reaction time is 5-6h, and the methacrylic acid modified epoxy resin is prepared.
[0015] Preferably, the silver powder has a D50 particle size of 0.5-2.5 microns and a specific surface area of 0.25-0.5 m 2 / g of spherical silver powder.
[0016] Preferably, the oxide nano-additive includes one or more of aluminum oxide, titanium oxide or zinc oxide, and the particle size of the oxide nano-additive is 5-30 nanometers.
[0017] Preferably, the thickener comprises polyisobutyl ester and modified hydroxyethyl cellulose in a weight ratio of 1:(1-3).
[0018] Preferably, the preparation method of modified hydroxyethyl cellulose comprises: weighing 0.5-3g hydroxyethyl cellulose and dissolving it in 20-60mL dehydrated dimethyl sulfoxide, then adding 0.5-2g ethylene oxide to the hydroxyethyl cellulose solution, stirring and heating the mixed solution to 50-70°C, adding 0.01-1g SnCl 4The mixture was reacted with 5-20 mL of dimethyl sulfoxide mixed solution as a catalyst for 0.1-1 h. After completion, the reaction solution was cooled to room temperature, and then the solvent DMSO was removed by solvent replacement with ethyl acetate and filtered to obtain a solid product. The solid product was redispersed in distilled water, dialyzed for 20-28 h, rotary evaporated until a small amount of water remained, and freeze-dried to obtain modified hydroxyethyl cellulose.
[0019] Preferably, the thixotropic agent is at least one of bentonite, calcium silicate, colloidal alumina and polyamide wax.
[0020] Preferably, the surfactant is Span 85.
[0021] Preferably, the wetting and dispersing agent is polyethylene wax.
[0022] Preferably, the epoxy resin comprises epoxy resin E-44 and epoxy resin E-51 in a weight ratio of 1:2, and the solvent comprises n-butanol and ethylene glycol butyl ether in a weight ratio of 2:1.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention uses organic solvent, methacrylic acid modified epoxy resin, auxiliary agent, silver powder and oxide nano additive as raw materials to prepare heterojunction silver paste; wherein the auxiliary agent includes a thickener, a toughening agent, a thixotropic agent, a surfactant and a wetting dispersant in a weight ratio of (1-4): (2-4): (2-5): (1-5): (1-5), the thixotropic agent is at least one of bentonite, calcium silicate, colloidal alumina and polyamide wax, the surfactant is Span 85, and the wetting dispersant is polyethylene wax. The raw materials and proportions specified in the present invention can effectively improve the performance of the heterojunction silver paste;
[0025] 2. The present invention uses terpineol, tributyl citrate, and ethyl acetate in a mass ratio of (2-3): (1-3): (1-2) as a mixed organic solvent, and uses methacrylic acid modified epoxy resin as a base resin, which effectively promotes close contact between the slurry and the substrate, promotes the slurry to form a bond between the substrates, and makes the silver paste better wet and penetrate into the surface of the substrate, which helps to form a tight silver paste / substrate interface and improve the overall performance of the heterojunction; wherein, the acrylate structural unit in the methacrylic acid modified epoxy resin can provide more cross-linking points, thereby improving the conductivity of the silver paste after curing, and the modified epoxy resin may also form a conductive network, further improving the conductive performance of the silver paste; based on this, a heterojunction silver paste with good adhesion, high filling factor, and good wettability can be finally obtained, which can also effectively improve the photoelectric conversion efficiency;
[0026] 3. The present invention also uses aluminum oxide, titanium oxide or zinc oxide with a particle size of 5-30 nanometers as an oxide nano-additive, which not only reduces the amount of silver powder used and reduces the production cost, but also improves the stability of the silver paste and effectively resists the influence of oxidation and environmental factors;
[0027] 4. The present invention uses polyisobutyl ester and modified hydroxyethyl cellulose thickeners in a weight ratio of 1: (1-3). Polyisobutyl ester, with its unique chemical structure, can form a network structure in the silver paste, thereby increasing its viscosity; and modified hydroxyethyl cellulose can also effectively increase the viscosity of the silver paste through the entanglement of its polymer chains. When the two are mixed in an appropriate ratio, a synergistic effect can be produced, so that the viscosity of the silver paste is further improved; in addition, ethylene oxide is used as a modifier in the present invention, and the prepared ethylene oxide-modified hydroxyethyl cellulose allows the silver particles in the silver paste to be more evenly distributed in the slurry, forming a denser conductive network, thereby improving the conductive performance of the heterojunction battery and reducing the resistance loss; and by improving the performance of the silver paste, the photoelectric conversion efficiency of the heterojunction battery can be indirectly improved;
[0028] 5. The preparation process adopted by the present invention is simple and efficient, which reduces the production cost and makes the heterojunction silver paste easier to promote and apply. Moreover, the heterojunction silver paste is suitable for a variety of electronic devices, such as solar cells, touch screens and LEDs, and has broad market prospects.
[0029] In summary, the present invention overcomes the deficiencies of the prior art, has a reasonable design, and has high social use value and application prospects. DETAILED DESCRIPTION
[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] This embodiment provides a method for preparing a heterojunction silver paste, the steps comprising:
[0033] (1) mixing 10 parts of an organic solvent, 4 parts of a methacrylic acid-modified epoxy resin, and 6 parts of an auxiliary agent at 45° C. and stirring for 50 minutes, and then cooling to room temperature to obtain an organic carrier;
[0034] The organic solvent comprises terpineol, tributyl citrate, and ethyl acetate in a mass ratio of (2.5):(2):(1.5);
[0035] The preparation method of the methacrylic acid modified epoxy resin comprises: using 32 parts of methacrylic acid as a functional monomer, using 0.8wt% of benzoyl peroxide as an initiator, 26 parts of butyl acrylate, 6 parts of styrene as raw materials and 12 parts of epoxy resin, carrying out graft polymerization in the presence of 38 parts of solvent, the reaction temperature is 115°C, the reaction time is 5.5h, and the methacrylic acid modified epoxy resin is prepared;
[0036] The auxiliary agent comprises a thickener, a toughening agent, a thixotropic agent, a surfactant and a wetting and dispersing agent in the weight ratio of (2): (3): (4): (3): (3);
[0037] The thickener comprises polyisobutyl ester and modified hydroxyethyl cellulose in a weight ratio of 1:(2); the thixotropic agent is bentonite; the surfactant is Span 85; the wetting and dispersing agent is polyethylene wax; the epoxy resin comprises epoxy resin E-44 and epoxy resin E-51 in a weight ratio of 1:2; the solvent comprises n-butanol and ethylene glycol butyl ether in a weight ratio of 2:1;
[0038] The preparation method of modified hydroxyethyl cellulose comprises: weighing 1g of hydroxyethyl cellulose and dissolving it in 40mL of dehydrated dimethyl sulfoxide, then adding 1g of ethylene oxide to the hydroxyethyl cellulose solution, stirring and heating the mixed solution to 60°C, adding 0.05g of SnCl 4 The mixture was reacted with 10 mL of dimethyl sulfoxide as a catalyst for 0.5 h. After completion, the reaction solution was cooled to room temperature, and then the solvent DMSO was removed by solvent replacement with ethyl acetate and filtered to obtain a solid product. The solid product was redispersed in distilled water, dialyzed for 24 h, rotary evaporated until a small amount of water remained, and freeze-dried to obtain modified hydroxyethyl cellulose;
[0039] (2) mixing 80 parts of silver powder and 12 parts of oxide nano-additives with the organic carrier prepared in step (1), and stirring and mixing them uniformly to prepare a silver paste;
[0040] The silver powder has a D50 particle size of 1.5 microns and a specific surface area of 0.4 m 2 / g of spherical silver powder; the oxide nano additive is aluminum oxide with a particle size of 18 nanometers.
[0041] Example 2
[0042] This embodiment provides a method for preparing a heterojunction silver paste, the steps comprising:
[0043] (1) mixing 11 parts of an organic solvent, 5 parts of a methacrylic acid-modified epoxy resin, and 5 parts of an auxiliary agent at 40° C. and stirring for 45 minutes, and then cooling to room temperature to obtain an organic carrier;
[0044] The organic solvent comprises terpineol, tributyl citrate, and ethyl acetate in a mass ratio of (2): (1): (2);
[0045] The preparation method of the methacrylic acid modified epoxy resin comprises: using 30 parts of methacrylic acid as a functional monomer, using 0.7wt% of benzoyl peroxide as an initiator, 25 parts of butyl acrylate, 5 parts of styrene as raw materials and 10 parts of epoxy resin, carrying out graft polymerization in the presence of 35 parts of solvent, the reaction temperature is 110°C, the reaction time is 6h, and the methacrylic acid modified epoxy resin is prepared;
[0046] The auxiliary agent comprises a thickener, a toughening agent, a thixotropic agent, a surfactant and a wetting and dispersing agent in the weight ratio of (1): (2): (2): (1): (1);
[0047] The thickener comprises polyisobutyl ester and modified hydroxyethyl cellulose in a weight ratio of 1:(1); the thixotropic agent is calcium silicate; the surfactant is Span 85; the wetting and dispersing agent is polyethylene wax; the epoxy resin comprises epoxy resin E-44 and epoxy resin E-51 in a weight ratio of 1:2; the solvent comprises n-butanol and ethylene glycol butyl ether in a weight ratio of 2:1;
[0048] The preparation method of modified hydroxyethyl cellulose comprises: weighing 1g of hydroxyethyl cellulose and dissolving it in 40mL of dehydrated dimethyl sulfoxide, then adding 1g of ethylene oxide to the hydroxyethyl cellulose solution, stirring and heating the mixed solution to 60°C, adding 0.05g of SnCl 4 The mixture was reacted with 10 mL of dimethyl sulfoxide as a catalyst for 0.5 h. After completion, the reaction solution was cooled to room temperature, and then the solvent DMSO was removed by solvent replacement with ethyl acetate and filtered to obtain a solid product. The solid product was redispersed in distilled water, dialyzed for 24 h, rotary evaporated until a small amount of water remained, and freeze-dried to obtain modified hydroxyethyl cellulose;
[0049] (2) mixing 90 parts of silver powder and 11 parts of oxide nano-additives with the organic carrier prepared in step (1), and stirring and mixing them uniformly to prepare a silver paste;
[0050] The silver powder has a D50 particle size of 0.5 microns and a specific surface area of 0.25 m 2 / g of spherical silver powder; the oxide nano additive is titanium oxide with a particle size of 10 nanometers.
[0051] Example 3
[0052] This embodiment provides a method for preparing a heterojunction silver paste, the steps comprising:
[0053] (1) mixing 12 parts of an organic solvent, 5 parts of a methacrylic acid-modified epoxy resin, and 3 parts of an auxiliary agent at 50° C. and stirring for 60 minutes, and then cooling to room temperature to obtain an organic carrier;
[0054] The organic solvent comprises terpineol, tributyl citrate, and ethyl acetate in a mass ratio of (3): (3): (2);
[0055] The preparation method of the methacrylic acid modified epoxy resin comprises: using 35 parts of methacrylic acid as a functional monomer, using 1wt% of benzoyl peroxide as an initiator, 28 parts of butyl acrylate, 8 parts of styrene as raw materials and 14 parts of epoxy resin, carrying out graft polymerization in the presence of 42 parts of solvent, the reaction temperature is 120°C, the reaction time is 6 hours, and the methacrylic acid modified epoxy resin is prepared;
[0056] The auxiliary agent comprises a thickener, a toughening agent, a thixotropic agent, a surfactant and a wetting and dispersing agent in a weight ratio of (4): (4): (5): (5): (5);
[0057] The thickener comprises polyisobutyl ester and modified hydroxyethyl cellulose in a weight ratio of 1:(3); the thixotropic agent is colloidal alumina; the surfactant is Span 85; the wetting and dispersing agent is polyethylene wax; the epoxy resin comprises epoxy resin E-44 and epoxy resin E-51 in a weight ratio of 1:2; the solvent comprises n-butanol and ethylene glycol butyl ether in a weight ratio of 2:1;
[0058] The preparation method of modified hydroxyethyl cellulose comprises: weighing 1g of hydroxyethyl cellulose and dissolving it in 40mL of dehydrated dimethyl sulfoxide, then adding 1g of ethylene oxide to the hydroxyethyl cellulose solution, stirring and heating the mixed solution to 60°C, adding 0.05g of SnCl 4 The mixture was reacted with 10 mL of dimethyl sulfoxide as a catalyst for 0.5 h. After completion, the reaction solution was cooled to room temperature, and then the solvent DMSO was removed by solvent replacement with ethyl acetate and filtered to obtain a solid product. The solid product was redispersed in distilled water, dialyzed for 24 h, rotary evaporated until a small amount of water remained, and freeze-dried to obtain modified hydroxyethyl cellulose;
[0059] (2) mixing 70 parts of silver powder and 14 parts of oxide nano-additives with the organic carrier prepared in step (1), and stirring and mixing them uniformly to prepare a silver paste;
[0060] The silver powder has a D50 particle size of 2.5 microns and a specific surface area of 0.5 m 2 / g of spherical silver powder; the oxide nano additive is zinc oxide with a particle size of 30 nanometers.
[0061] Example 4
[0062] This embodiment provides a method for preparing a heterojunction silver paste, the steps comprising:
[0063] (1) 14 parts of an organic solvent, 6 parts of a methacrylic acid-modified epoxy resin, and 8 parts of an auxiliary agent were mixed and stirred at 40° C. for 60 minutes, and then cooled to room temperature to obtain an organic carrier;
[0064] The organic solvent comprises terpineol, tributyl citrate, and ethyl acetate in a mass ratio of (2): (1): (2);
[0065] The preparation method of the methacrylic acid modified epoxy resin comprises: using 35 parts of methacrylic acid as a functional monomer, using 0.9wt% of benzoyl peroxide as an initiator, 26 parts of butyl acrylate, 7 parts of styrene as raw materials and 11 parts of epoxy resin, carrying out graft polymerization in the presence of 40 parts of solvent, the reaction temperature is 115°C, the reaction time is 5h, and the methacrylic acid modified epoxy resin is prepared;
[0066] The auxiliary agent comprises a thickener, a toughening agent, a thixotropic agent, a surfactant and a wetting and dispersing agent in the weight ratio of (1): (3): (5): (1): (3);
[0067] The thickener comprises polyisobutyl ester and modified hydroxyethyl cellulose in a weight ratio of 1:(2); the thixotropic agent is polyamide wax; the surfactant is Span 85; the wetting dispersant is polyethylene wax; the epoxy resin comprises epoxy resin E-44 and epoxy resin E-51 in a weight ratio of 1:2; the solvent comprises n-butanol and ethylene glycol butyl ether in a weight ratio of 2:1;
[0068] The preparation method of modified hydroxyethyl cellulose comprises: weighing 1g of hydroxyethyl cellulose and dissolving it in 40mL of dehydrated dimethyl sulfoxide, then adding 1g of ethylene oxide to the hydroxyethyl cellulose solution, stirring and heating the mixed solution to 60°C, adding 0.05g of SnCl 4 The mixture was reacted with 10 mL of dimethyl sulfoxide as a catalyst for 0.5 h. After completion, the reaction solution was cooled to room temperature, and then the solvent DMSO was removed by solvent replacement with ethyl acetate and filtered to obtain a solid product. The solid product was redispersed in distilled water, dialyzed for 24 h, rotary evaporated until a small amount of water remained, and freeze-dried to obtain modified hydroxyethyl cellulose;
[0069] (2) mixing 82 parts of silver powder and 11 parts of oxide nano-additives with the organic carrier prepared in step (1), and stirring and mixing them uniformly to prepare a silver paste;
[0070] The silver powder has a D50 particle size of 2 microns and a specific surface area of 0.4 m 2 / g of spherical silver powder; the oxide nano additive is aluminum oxide with a particle size of 20 nanometers.
[0071] Comparative Example 1
[0072] This embodiment provides a method for preparing a heterojunction silver paste, the steps comprising:
[0073] (1) mixing 10 parts of an organic solvent, 4 parts of an epoxy resin, and 6 parts of an additive at 45° C. and stirring for 50 minutes, and then cooling to room temperature to obtain an organic carrier;
[0074] The organic solvent comprises terpineol, tributyl citrate, and ethyl acetate in a mass ratio of (2.5):(2):(1.5);
[0075] The preparation method of the methacrylic acid modified epoxy resin comprises: using 32 parts of methacrylic acid as a functional monomer, using 0.8wt% of benzoyl peroxide as an initiator, 26 parts of butyl acrylate, 6 parts of styrene as raw materials and 12 parts of epoxy resin, carrying out graft polymerization in the presence of 38 parts of solvent, the reaction temperature is 115°C, the reaction time is 5.5h, and the methacrylic acid modified epoxy resin is prepared;
[0076] The auxiliary agent comprises a thickener, a toughening agent, a thixotropic agent, a surfactant and a wetting and dispersing agent in the weight ratio of (2): (3): (4): (3): (3);
[0077] The thickener comprises polyisobutyl ester and modified hydroxyethyl cellulose in a weight ratio of 1:(2); the thixotropic agent is bentonite; the surfactant is Span 85; the wetting and dispersing agent is polyethylene wax; wherein the preparation method of the modified hydroxyethyl cellulose comprises: weighing 1g of hydroxyethyl cellulose and dissolving it in 40mL of dehydrated dimethyl sulfoxide, then adding 1g of ethylene oxide to the hydroxyethyl cellulose solution, stirring and heating the mixed solution to 60°C, adding 0.05g of SnCl 4 The mixture was reacted with 10 mL of dimethyl sulfoxide as a catalyst for 0.5 h. After completion, the reaction solution was cooled to room temperature, and then the solvent DMSO was removed by solvent replacement with ethyl acetate and filtered to obtain a solid product. The solid product was redispersed in distilled water, dialyzed for 24 h, rotary evaporated until a small amount of water remained, and freeze-dried to obtain modified hydroxyethyl cellulose;
[0078] The epoxy resin includes epoxy resin E-44 and epoxy resin E-51 in a weight ratio of 1:2;
[0079] (2) mixing 80 parts of silver powder and 12 parts of oxide nano-additives with the organic carrier prepared in step (1), and stirring and mixing them uniformly to prepare a silver paste;
[0080] The silver powder has a D50 particle size of 1.5 microns and a specific surface area of 0.4 m 2 / g of spherical silver powder; the oxide nano additive is aluminum oxide with a particle size of 18 nanometers.
[0081] Comparative Example 2
[0082] This embodiment provides a method for preparing a heterojunction silver paste, the steps comprising:
[0083] (1) mixing 10 parts of an organic solvent, 4 parts of a methacrylic acid-modified epoxy resin, and 6 parts of an auxiliary agent at 45° C. and stirring for 50 minutes, and then cooling to room temperature to obtain an organic carrier;
[0084] The organic solvent comprises terpineol, tributyl citrate, and ethyl acetate in a mass ratio of (2.5):(2):(1.5);
[0085] The preparation method of the methacrylic acid modified epoxy resin comprises: using 32 parts of methacrylic acid as a functional monomer, using 0.8wt% of benzoyl peroxide as an initiator, 26 parts of butyl acrylate, 6 parts of styrene as raw materials and 12 parts of epoxy resin, carrying out graft polymerization in the presence of 38 parts of solvent, the reaction temperature is 115°C, the reaction time is 5.5h, and the methacrylic acid modified epoxy resin is prepared;
[0086] The auxiliary agent comprises a thickener, a toughening agent, a thixotropic agent, a surfactant and a wetting and dispersing agent in the weight ratio of (2): (3): (4): (3): (3);
[0087] The thickener comprises polyisobutyl ester and modified hydroxyethyl cellulose in a weight ratio of 1:(2); the thixotropic agent is bentonite; the surfactant is Span 85; the wetting and dispersing agent is polyethylene wax; the epoxy resin is epoxy resin E-44, and the solvent is n-butanol; wherein the preparation method of the modified hydroxyethyl cellulose comprises: weighing 1g of hydroxyethyl cellulose and dissolving it in 40mL of dehydrated dimethyl sulfoxide, then adding 1g of ethylene oxide to the hydroxyethyl cellulose solution, stirring and heating the mixed solution to 60°C, adding 0.05g of SnCl 4 The mixture was reacted with 10 mL of dimethyl sulfoxide as a catalyst for 0.5 h. After completion, the reaction solution was cooled to room temperature, and then the solvent DMSO was removed by solvent replacement with ethyl acetate and filtered to obtain a solid product. The solid product was redispersed in distilled water, dialyzed for 24 h, rotary evaporated until a small amount of water remained, and freeze-dried to obtain modified hydroxyethyl cellulose;
[0088] (2) mixing 80 parts of silver powder and 12 parts of oxide nano-additives with the organic carrier prepared in step (1), and stirring and mixing them uniformly to prepare a silver paste;
[0089] The silver powder has a D50 particle size of 1.5 microns and a specific surface area of 0.4 m 2 / g of spherical silver powder; the oxide nano additive is aluminum oxide with a particle size of 18 nanometers.
[0090] Comparative Example 3
[0091] This embodiment provides a method for preparing a heterojunction silver paste, the steps comprising:
[0092] (1) mixing 10 parts of an organic solvent, 4 parts of a methacrylic acid-modified epoxy resin, and 6 parts of an auxiliary agent at 45° C. and stirring for 50 minutes, and then cooling to room temperature to obtain an organic carrier;
[0093] The organic solvent comprises terpineol, tributyl citrate, and ethyl acetate in a mass ratio of (2.5):(2):(1.5);
[0094] The preparation method of the methacrylic acid modified epoxy resin comprises: using 32 parts of methacrylic acid as a functional monomer, using 0.8wt% of benzoyl peroxide as an initiator, 26 parts of butyl acrylate, 6 parts of styrene as raw materials and 12 parts of epoxy resin, carrying out graft polymerization in the presence of 38 parts of solvent, the reaction temperature is 115°C, the reaction time is 5.5h, and the methacrylic acid modified epoxy resin is prepared;
[0095] The auxiliary agent comprises a thickener, a toughening agent, a thixotropic agent, a surfactant and a wetting and dispersing agent in the weight ratio of (2): (3): (4): (3): (3);
[0096] The thickener comprises polyisobutyl ester and modified hydroxyethyl cellulose in a weight ratio of 1:(2); the thixotropic agent is bentonite; the surfactant is Span 85; the wetting and dispersing agent is polyethylene wax; the epoxy resin is epoxy resin E-51, and the solvent is ethylene glycol butyl ether; wherein the preparation method of the modified hydroxyethyl cellulose comprises: weighing 1g of hydroxyethyl cellulose and dissolving it in 40mL of dehydrated dimethyl sulfoxide, then adding 1g of ethylene oxide to the hydroxyethyl cellulose solution, stirring and heating the mixed solution to 60°C, adding 0.05g of SnCl 4 The mixture was reacted with 10 mL of dimethyl sulfoxide as a catalyst for 0.5 h. After completion, the reaction solution was cooled to room temperature, and then the solvent DMSO was removed by solvent replacement with ethyl acetate and filtered to obtain a solid product. The solid product was redispersed in distilled water, dialyzed for 24 h, rotary evaporated until a small amount of water remained, and freeze-dried to obtain modified hydroxyethyl cellulose;
[0097] (2) mixing 80 parts of silver powder and 12 parts of oxide nano-additives with the organic carrier prepared in step (1), and stirring and mixing them uniformly to prepare a silver paste;
[0098] The silver powder has a D50 particle size of 1.5 microns and a specific surface area of 0.4 m 2 / g of spherical silver powder; the oxide nano additive is aluminum oxide with a particle size of 18 nanometers.
[0099] Comparative Example 4
[0100] This embodiment provides a method for preparing a heterojunction silver paste, the steps comprising:
[0101] (1) mixing 10 parts of an organic solvent, 4 parts of a methacrylic acid-modified epoxy resin, and 6 parts of an auxiliary agent at 45° C. and stirring for 50 minutes, and then cooling to room temperature to obtain an organic carrier;
[0102] wherein the organic solvent comprises, by mass ratio (2.5): (2) terpineol and tributyl citrate;
[0103] The preparation method of the methacrylic acid modified epoxy resin comprises: using 32 parts of methacrylic acid as a functional monomer, using 0.8wt% of benzoyl peroxide as an initiator, 26 parts of butyl acrylate, 6 parts of styrene as raw materials and 12 parts of epoxy resin, carrying out graft polymerization in the presence of 38 parts of solvent, the reaction temperature is 115°C, the reaction time is 5.5h, and the methacrylic acid modified epoxy resin is prepared;
[0104] The auxiliary agent comprises a thickener, a toughening agent, a thixotropic agent, a surfactant and a wetting and dispersing agent in the weight ratio of (2): (3): (4): (3): (3);
[0105] The thickener comprises polyisobutyl ester and modified hydroxyethyl cellulose in a weight ratio of 1:(2); the thixotropic agent is bentonite; the surfactant is Span 85; the wetting and dispersing agent is polyethylene wax; the epoxy resin comprises epoxy resin E-44 and epoxy resin E-51 in a weight ratio of 1:2; the solvent comprises n-butanol and ethylene glycol butyl ether in a weight ratio of 2:1; wherein the preparation method of the modified hydroxyethyl cellulose comprises: weighing 1g of hydroxyethyl cellulose and dissolving it in 40mL of dehydrated dimethyl sulfoxide, then adding 1g of ethylene oxide to the hydroxyethyl cellulose solution, stirring and heating the mixed solution to 60°C, adding 0.05g of SnCl 4 The mixture was reacted with 10 mL of dimethyl sulfoxide as a catalyst for 0.5 h. After completion, the reaction solution was cooled to room temperature, and then the solvent DMSO was removed by solvent replacement with ethyl acetate and filtered to obtain a solid product. The solid product was redispersed in distilled water, dialyzed for 24 h, rotary evaporated until a small amount of water remained, and freeze-dried to obtain modified hydroxyethyl cellulose;
[0106] (2) mixing 80 parts of silver powder and 12 parts of oxide nano-additives with the organic carrier prepared in step (1), and stirring and mixing them uniformly to prepare a silver paste;
[0107] The silver powder has a D50 particle size of 1.5 microns and a specific surface area of 0.4 m 2 / g of spherical silver powder; the oxide nano additive is aluminum oxide with a particle size of 18 nanometers.
[0108] Comparative Example 5
[0109] This embodiment provides a method for preparing a heterojunction silver paste, the steps comprising:
[0110] (1) mixing 10 parts of an organic solvent, 4 parts of a methacrylic acid-modified epoxy resin, and 6 parts of an auxiliary agent at 45° C. and stirring for 50 minutes, and then cooling to room temperature to obtain an organic carrier;
[0111] The organic solvent comprises terpineol, tributyl citrate, and ethyl acetate in a mass ratio of (2.5):(2):(1.5);
[0112] The preparation method of the methacrylic acid modified epoxy resin comprises: using 32 parts of methacrylic acid as a functional monomer, using 0.8wt% of benzoyl peroxide as an initiator, 26 parts of butyl acrylate, 6 parts of styrene as raw materials and 12 parts of epoxy resin, carrying out graft polymerization in the presence of 38 parts of solvent, the reaction temperature is 115°C, the reaction time is 5.5h, and the methacrylic acid modified epoxy resin is prepared;
[0113] The auxiliary agent comprises a thickener, a toughening agent, a thixotropic agent, a surfactant and a wetting and dispersing agent in the weight ratio of (2): (3): (4): (3): (3);
[0114] The thickener comprises polyisobutyl ester and modified hydroxyethyl cellulose in a weight ratio of 1:(2); the thixotropic agent is bentonite; the surfactant is Span 85; the wetting and dispersing agent is polyethylene wax; the epoxy resin comprises epoxy resin E-44 and epoxy resin E-51 in a weight ratio of 1:2; the solvent comprises n-butanol and ethylene glycol butyl ether in a weight ratio of 2:1;
[0115] The preparation method of modified hydroxyethyl cellulose comprises: weighing 1g of hydroxyethyl cellulose and dissolving it in 40mL of dehydrated dimethyl sulfoxide, then adding 1g of ethylene oxide to the hydroxyethyl cellulose solution, stirring and heating the mixed solution to 60°C, adding 0.05g of SnCl 4The mixture was reacted with 10 mL of dimethyl sulfoxide as a catalyst for 0.5 h. After completion, the reaction solution was cooled to room temperature, and then the solvent DMSO was removed by solvent replacement with ethyl acetate and filtered to obtain a solid product. The solid product was redispersed in distilled water, dialyzed for 24 h, rotary evaporated until a small amount of water remained, and freeze-dried to obtain modified hydroxyethyl cellulose;
[0116] (2) mixing 80 parts of silver powder and 12 parts of oxide nano-additives with the organic carrier prepared in step (1), and stirring and mixing them uniformly to prepare a silver paste;
[0117] The silver powder has a D50 particle size of 1.5 microns and a specific surface area of 0.4 m 2 / g of spherical silver powder; the oxide nano additive is copper oxide with a particle size of 18 nanometers.
[0118] Comparative Example 6
[0119] This embodiment provides a method for preparing a heterojunction silver paste, the steps comprising:
[0120] (1) mixing 10 parts of an organic solvent, 4 parts of a methacrylic acid-modified epoxy resin, and 6 parts of an auxiliary agent at 45° C. and stirring for 50 minutes, and then cooling to room temperature to obtain an organic carrier;
[0121] The organic solvent comprises terpineol, tributyl citrate, and ethyl acetate in a mass ratio of (2.5):(2):(1.5);
[0122] The preparation method of the methacrylic acid modified epoxy resin comprises: using 32 parts of methacrylic acid as a functional monomer, using 0.8wt% of benzoyl peroxide as an initiator, 26 parts of butyl acrylate, 6 parts of styrene as raw materials and 12 parts of epoxy resin, carrying out graft polymerization in the presence of 38 parts of solvent, the reaction temperature is 115°C, the reaction time is 5.5h, and the methacrylic acid modified epoxy resin is prepared;
[0123] The auxiliary agent comprises a thickener, a toughening agent, a thixotropic agent, a surfactant and a wetting and dispersing agent in the weight ratio of (2): (3): (4): (3): (3);
[0124] The thickener is polyisobutyl ester; the thixotropic agent is bentonite; the surfactant is Span 85; the wetting and dispersing agent is polyethylene wax; the epoxy resin includes epoxy resin E-44 and epoxy resin E-51 in a weight ratio of 1:2, and the solvent includes n-butanol and ethylene glycol butyl ether in a weight ratio of 2:1;
[0125] (2) mixing 80 parts of silver powder and 12 parts of oxide nano-additives with the organic carrier prepared in step (1), and stirring and mixing them uniformly to prepare a silver paste;
[0126] The silver powder has a D50 particle size of 1.5 microns and a specific surface area of 0.4 m 2 / g of spherical silver powder; the oxide nano additive is aluminum oxide with a particle size of 18 nanometers.
[0127] Comparative Example 7
[0128] This embodiment provides a method for preparing a heterojunction silver paste, the steps comprising:
[0129] (1) mixing 10 parts of an organic solvent, 4 parts of a methacrylic acid-modified epoxy resin, and 6 parts of an auxiliary agent at 45° C. and stirring for 50 minutes, and then cooling to room temperature to obtain an organic carrier;
[0130] The organic solvent comprises terpineol, tributyl citrate, and ethyl acetate in a mass ratio of (2.5):(2):(1.5);
[0131] The preparation method of the methacrylic acid modified epoxy resin comprises: using 32 parts of methacrylic acid as a functional monomer, using 0.8wt% of benzoyl peroxide as an initiator, 26 parts of butyl acrylate, 6 parts of styrene as raw materials and 12 parts of epoxy resin, carrying out graft polymerization in the presence of 38 parts of solvent, the reaction temperature is 115°C, the reaction time is 5.5h, and the methacrylic acid modified epoxy resin is prepared;
[0132] The auxiliary agent comprises a thickener, a toughening agent, a thixotropic agent, a surfactant and a wetting and dispersing agent in the weight ratio of (2): (3): (4): (3): (3);
[0133] The thickener is modified hydroxyethyl cellulose; the thixotropic agent is bentonite; the surfactant is Span 85; the wetting and dispersing agent is polyethylene wax; the epoxy resin includes epoxy resin E-44 and epoxy resin E-51 in a weight ratio of 1:2, and the solvent includes n-butanol and ethylene glycol butyl ether in a weight ratio of 2:1;
[0134] The preparation method of modified hydroxyethyl cellulose comprises: weighing 1g of hydroxyethyl cellulose and dissolving it in 40mL of dehydrated dimethyl sulfoxide, then adding 1g of ethylene oxide to the hydroxyethyl cellulose solution, stirring and heating the mixed solution to 60°C, adding 0.05g of SnCl 4 The mixture was reacted with 10 mL of dimethyl sulfoxide as a catalyst for 0.5 h. After completion, the reaction solution was cooled to room temperature, and then the solvent DMSO was removed by solvent replacement with ethyl acetate and filtered to obtain a solid product. The solid product was redispersed in distilled water, dialyzed for 24 h, rotary evaporated until a small amount of water remained, and freeze-dried to obtain modified hydroxyethyl cellulose;
[0135] (2) mixing 80 parts of silver powder and 12 parts of oxide nano-additives with the organic carrier prepared in step (1), and stirring and mixing them uniformly to prepare a silver paste;
[0136] The silver powder has a D50 particle size of 1.5 microns and a specific surface area of 0.4 m 2 / g of spherical silver powder; the oxide nano additive is aluminum oxide with a particle size of 18 nanometers.
[0137] Comparative Example 8
[0138] This embodiment provides a method for preparing a heterojunction silver paste, the steps comprising:
[0139] (1) mixing 10 parts of an organic solvent, 4 parts of a methacrylic acid-modified epoxy resin, and 6 parts of an auxiliary agent at 45° C. and stirring for 50 minutes, and then cooling to room temperature to obtain an organic carrier;
[0140] The organic solvent comprises terpineol, tributyl citrate, and ethyl acetate in a mass ratio of (2.5):(2):(1.5);
[0141] The preparation method of the methacrylic acid modified epoxy resin comprises: using 32 parts of methacrylic acid as a functional monomer, using 0.8wt% of benzoyl peroxide as an initiator, 26 parts of butyl acrylate, 6 parts of styrene as raw materials and 12 parts of epoxy resin, carrying out graft polymerization in the presence of 38 parts of solvent, the reaction temperature is 115°C, the reaction time is 5.5h, and the methacrylic acid modified epoxy resin is prepared;
[0142] The auxiliary agent comprises a toughening agent, a thixotropic agent, a surfactant and a wetting and dispersing agent in a weight ratio of (3): (4): (3): (3);
[0143] The thixotropic agent is bentonite; the surfactant is Span 85; the wetting and dispersing agent is polyethylene wax; the epoxy resin includes epoxy resin E-44 and epoxy resin E-51 in a weight ratio of 1:2, and the solvent includes n-butanol and ethylene glycol butyl ether in a weight ratio of 2:1;
[0144] (2) mixing 80 parts of silver powder and 12 parts of oxide nano-additives with the organic carrier prepared in step (1), and stirring and mixing them uniformly to prepare a silver paste;
[0145] The silver powder has a D50 particle size of 1.5 microns and a specific surface area of 0.4 m 2 / g of spherical silver powder; the oxide nano additive is aluminum oxide with a particle size of 18 nanometers.
[0146] Performance testing method:
[0147] (1) Measuring the volume resistivity of the slurries prepared in Examples 1-4 and Comparative Examples 1-8;
[0148] (2) The silver paste was coated on the crystalline silicon heterojunction battery by screen printing, and then dried at 200° C. for 8 min and cured at 200° C. for 20 min. Then, the photoelectric conversion efficiency, open circuit voltage, and series resistance of the battery were measured using a device model HSC1 / XSCM-9 produced by Shanghai Jiaotong University Heshuang Technology Co., Ltd.;
[0149] (3) The adhesion of the conductive silver paste is determined by the 100-grid test method. The conductive silver paste is printed or applied on the surface of the ITO substrate. After drying, the adhesion is measured according to the national standard "GBT9286-1998 Scratch Test for Paint and Varnish Films". That is, a 100-grid knife is used to scratch 100 small grids of 1 mm × 1 mm on the surface of the test sample. Each scratch line should reach the surface of the ITO substrate. The debris in the test area is brushed clean with a brush. The 3M600 tape produced by 3M Company of the United States or an adhesive of equivalent effectiveness is used. The tape is firmly adhered to the small grid to be tested, and the tape is vigorously rubbed with an eraser to increase the contact area and strength between the tape and the tested area; Grasp one end of the tape with your hand, and quickly pull off the tape in the vertical direction of the tape, and observe the ratio of the adhered part to the number of grids; When the edge of the cut (cut) is completely smooth and there is no peeling on the edge of the grid, the adhesion of the conductive silver paste is judged to be 5B; When there is a small piece of peeling at the intersection of the cut, and the actual damage in the grid area is ≤5%, the adhesion of the conductive silver paste is judged to be 4B;
[0150] (4) Evaluate the wear resistance (scratching times) of the slurry. The wear resistance test method is as follows: evenly apply the slurry on the substrate, with an electrode thickness of ≤25 μm. After curing according to the process conditions, use a friction rod with a smooth round bottom (1 mm in diameter) to rub the electrode surface back and forth. Observe the changes on the electrode surface until it falls off, and record the friction times. The specific friction times are the average values of three samples tested.
[0151] The specific test results of the above tests are shown in Table 1 below:
[0152] Table 1
[0153]
[0154]
[0155] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a heterojunction silver paste, characterized in that the steps include: (1) Mixing 8-14 parts of an organic solvent, 2-6 parts of a methacrylic acid-modified epoxy resin, and 2-10 parts of an auxiliary agent at 40-50° C. and stirring for 40-60 minutes, and then cooling to room temperature to obtain an organic carrier; (2) mixing 20-95 parts of silver powder and 10-15 parts of oxide nano-additives with the organic carrier prepared in step (1), and stirring and mixing them evenly to prepare a silver paste; The auxiliary agent includes a thickener, a toughening agent, a thixotropic agent, a surfactant and a wetting and dispersing agent in a weight ratio of (1-4): (2-4): (2-5): (1-5): (1-5); The organic solvent comprises terpineol, tributyl citrate, and ethyl acetate in a mass ratio of (2-3): (1-3): (1-2); The preparation method of the methacrylic acid modified epoxy resin comprises: using 30-35 parts of methacrylic acid as a functional monomer, using 0.7-1wt% of benzoyl peroxide as an initiator, 25-28 parts of butyl acrylate, 5-8 parts of styrene as raw materials and 10-14 parts of epoxy resin, carrying out graft polymerization in the presence of 35-42 parts of a solvent, the reaction temperature is 110-120° C., the reaction time is 5-6 hours, and the methacrylic acid modified epoxy resin is prepared; The thickener comprises polyisobutyl ester and modified hydroxyethyl cellulose in a weight ratio of 1:(1-3); The preparation method of the modified hydroxyethyl cellulose comprises: dissolving hydroxyethyl cellulose in dehydrated dimethyl sulfoxide, then adding ethylene oxide to the hydroxyethyl cellulose solution, heating the mixed solution to 50-70° C. by mechanical stirring, adding a mixed solution of SnCl4 and dimethyl sulfoxide as a catalyst, cooling to room temperature after the reaction is completed, performing solvent replacement with ethyl acetate to remove the solvent and suction filtering, redispersing the solid product in distilled water for dialysis, rotary evaporation, and freeze drying to obtain the modified hydroxyethyl cellulose; the solvent comprises n-butanol and ethylene glycol butyl ether in a weight ratio of 2:1; The epoxy resin includes epoxy resin E-44 and epoxy resin E-51 in a weight ratio of 1:
2.
2. The method for preparing a heterojunction silver paste according to claim 1, characterized in that: The silver powder has a D50 particle size of 0.5-2.5 microns and a specific surface area of 0.25-0.5 m 2 / g of spherical silver powder.
3. The method for preparing a heterojunction silver paste according to claim 1, characterized in that: The oxide nano-additive includes one or more of aluminum oxide, titanium oxide or zinc oxide, and the particle size of the oxide nano-additive is 5-30 nanometers.
4. The method for preparing a heterojunction silver paste according to claim 1, characterized in that: The thixotropic agent is at least one of bentonite, calcium silicate, colloidal alumina and polyamide wax; the surfactant is Span 85, and the wetting dispersant is polyethylene wax.
